Research Progress Concerning Dual Blockade of Lymphocyte-Activation Gene 3 and Programmed Death-1/Programmed Death-1 Ligand-1 Blockade in Cancer Immunotherapy: Preclinical and Clinical Evidence of This Potentially More Effective Immunotherapy Strategy - Qi, Yihang; Chen, Li; Liu, Qiang; Kong, Xiangyi; Fang, Yi; Wang, Jing (Frontiers in Immunology, 2021)
Although various immunotherapies have exerted promising effects on cancer treatment, many patients with cancer continue to exhibit poor responses. Because of its negative regulatory effects on T cells and its biological functions related to immune and inflammatory responses, there has been considerable emphasis on a protein-coding gene named lymphocyte-activation gene 3 (LAG3). Recently, evidence demonstrated marked synergy in its targeted therapy with programmed death-1 and programmed death-1 ligand-1 (PD-1/PD-L1) blockade, and a variety of LAG3 targeted agents are in clinical trials, indicating the important role of LAG3 in immunotherapy. This mini-review discusses preclinical and clinical studies investigating PD-1 pathway blockade in combination with LAG3 inhibition as a potential more effective immunotherapy strategy for further development in the clinic. This strategy might provide a new approach for the design of more effective and precise cancer immune checkpoint therapies.